Simulation of Suppression of Gamma Sensitivity of 'Fission Electron-Collection' Neutron Detector*Supported by the National Natural Science Foundation of China under Grant No 11205141, and the Science and Technology Foundation of China Academy of Engineering Physics under Grant No 2012B0103003. (May 2016) - Wang 王, Dong 栋; Zhang 张, Chuan-Fei 传飞; Li 李, Bo-Jun 波均; Cai 蔡, Yi-Ping 易平; Zhu 朱, Xue-Bin 学彬; Si 司, Fen-Ni 粉妮; Xi 席, Zhi-Guo 治国
Abstract : The fission electron-collection neutron detector (FECND) is a current-type neutron detector. Based on the analysis of the generation process of the gamma signals of the FECND, a mechanism utilizing symmetrical structure is proposed and discussed to suppress the gamma signals. According to this mechanism, the electrons generated from the gamma rays can be well compensated for by the adjustment of the electrodes' thickness and distance. In this study, based on the Monte–Carlo simulation of the gamma signals of the FECND, the varying patterns are obtained between the gamma signals and the detector parameter settings. As indicated by the simulation results, the gamma electrons can be compensated for completely by simply adjusting the coated electrode substrate thickness and distance. Moreover, with a proposed optimal parameter setting, the gamma sensitivity can be as low as 3.39×10 −23 C·cm 2, while the signal-to-noise ratio can be higher than 200:1. The compensation results of the γ-rays in the FECND will be slightly affected by the manufacturing error or the assembly error.